2019
DOI: 10.1111/ijac.13198
|View full text |Cite
|
Sign up to set email alerts
|

Black ceramic coatings on Ti alloy with enhanced high absorptivity and high emissivity by plasma electrolytic oxidation

Abstract: A black ceramic coating with high absorptivity and emissivity was successfully prepared on TA7 (Ti‐5Al‐2.5Sn) in a hybrid electrolyte solution by plasma electrolytic oxidation for improving the imaging precision of optical system. The influence of electrolyte components and technical parameters on the composition, structure, and optical properties was investigated. The results show the coatings with typically porous structure are mainly composed of O, P, Si, Ti, V, Fe, and Ni. The corresponding amorhous oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The blackness of the coatings is affected by anions such as VO 3− , WO 2− 4 , MoO 2− 4 and transition metal cations such as Fe 2+ , Fe 3+ , Cu 2+ , Co 2+ , Ni 2+ and Zr 4+ , according to the literature [19,26,34]. Regarding our present study, additives based on molybdenum and iron were used.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The blackness of the coatings is affected by anions such as VO 3− , WO 2− 4 , MoO 2− 4 and transition metal cations such as Fe 2+ , Fe 3+ , Cu 2+ , Co 2+ , Ni 2+ and Zr 4+ , according to the literature [19,26,34]. Regarding our present study, additives based on molybdenum and iron were used.…”
Section: Discussionmentioning
confidence: 99%
“…Absorptance (α) was determined from the reflectance spectra of the coatings, according to Equation (1) (see Methods). The lower the reflectance is, the better the absorptance is [34]. Based on the spectra in Figure 2, all prepared coatings reflect almost 10% of light in the visible range, with a maximum reflectance in the NIR range of about 35%.…”
Section: Optical Measurementsmentioning
confidence: 95%
See 2 more Smart Citations
“…The surface absorption performance of ceramic coating is directly related to coating thickness, surface roughness, material microstructure, and composition. Previous studies have shown that these parameters are mainly affected by the power mode, electrolyte composition, power parameters, and oxidation time of PEO technology [36][37][38]. Therefore, the above factors affecting the surface absorption properties of ceramic coatings were investigated in this paper.…”
Section: Preparation and Characteristics Of High-absorption Ceramic Coatingmentioning
confidence: 99%